Historical and technical insight into the human motifs in the glass sculpture - Villegas-Broncano, Maria A.; Durán-Suárez, J. Alberto (Arte, Individuo y Sociedad, 2021)
Although glass proto-sculptures were made with deep artistic value since the most remote times, in the late 19th century the glass sculpture was developed, and during the 20th century the Studio Glass Movement reached the maximum level of technical perfection and aesthetic variety. The scientific and technical glass knowledge contributed to achieve appropriate hot and cold working procedures, and the artists improved their designs and creations. This paper focuses on the binomial glass sculpture and human motifs. The historic evolution of the glass sculpture with human motifs is analyzed, taking into account the production techniques and the relationships between the glass work and the expression of the finished artwork. A set of sculptures and sculptors are shown as representative examples of the main historical periods in which the glass plays an important role in the sculpture scene. The human representation in the glass sculpture can be considered as a constant throughout centuries, even though it is not the most frequent creative or ornamental motif. Either figurative or abstract human references can be found, although the former are the majority. This tendency is also present in the contemporary Studio Glass Movement sculptures.